I even funnier - Patterson, James, 1947-; Grabenstein, Chris; Park, Laura, 1980- (New York : Little, Brown and Co., 2013)
While on a mission to win the Planet's Funniest Kid Comic regional competition, New York middle schooler Jamie Grimm copes with rival comics and bullies, a buddy in trouble, and a sudden family emergency, all with a sense of humor and a loyal group of friends.
4.4
3-6
710L
T
Keywords: Comedians -- Juvenile fiction; Contests -- Juvenile fiction; People with disabilities -- Juvenile fiction; Bullies -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Comedians -- Fiction; Contests -- Fiction; People with disabilities -- Fiction; Bullies -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Humorous stories; Comedians -- Fiction; Contests -- Fiction; People with disabilities -- Fiction; Bullies -- Fiction; Middle schools -- Fiction; School stories; Comedians -- Fiction; Contests -- Fiction; People with disabilities -- Fiction; Bullying -- Fiction; Middle schools -- Fiction; Humorous stories; Long Beach (N.Y.) -- Juvenile fiction; Long Beach (N.Y.) -- Fiction; Long Beach (N.Y.) -- Fiction; Long Beach (N.Y.) -- Fiction; Humorous fiction